Developing supply chain strategy for the Success in the Implementation of Maintenance and Preventive Repair at the Kavir Steel Complex - Mohsen Ghobadi (International Journal of Supply Chain Management, 2019)
Abstract- An important issue in preventive maintenance is maintaining the readiness and operational maintenance of equipment, machinery and facilities by using supply chain management strategy. Utilizing the maintenance planning system, while creating the most desirable repair services and adopting the best practices for continuing industry work with maximum efficiency and reducing costs, will increase investment in the industry, in the absence of restrictions on resources and raw materials. To use this system, it is necessary to identify some important and influential factors in its implementation, in order to obtain useful results in its implementation, which is always associated with costs. In this research, it is attempted to investigate some of these important factors in the Kavir Steel Complex Company. In this regard, through the question, a set of views of managers and relevant experts will be examined, and finally, the most important success factors in the implementation of preventive maintenance in the industry will be sought.